2020
DOI: 10.3168/jds.2019-17804
|View full text |Cite
|
Sign up to set email alerts
|

Symposium review: Considerations for the future of dairy cattle housing: An animal welfare perspective

Abstract: Many contemporary dairy cattle housing practices are at odds with societal perceptions of positive animal welfare. The public (i.e., those external to the dairy industry) typically emphasizes the importance of naturalness for dairy cattle, such as through provision of pasture, freedom of movement, and the ability to interact socially with conspecifics. Yet, in the United States, the majority of lactating dairy cattle are reportedly housed without any access to pasture, and almost 39% of dairy farms use tiestal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 122 publications
0
32
0
1
Order By: Relevance
“…Surprisingly little research has assessed public values about surplus dairy calves. When asked about food animal agriculture in general, the public strongly values naturalness, such as pasture access as well as indoor environments that allow for the expression of natural behavior, freedom of movement and socializing with companions [reviewed by (117,118)]. The current system for rearing surplus dairy calves is heavily reliant on unnatural housing (e.g., indoor housing with mechanical ventilation or outdoor housing with low space allowance), isolated social environments (e.g., individual pens), and inadequate feeding programs (low milk allowances compared to what they would drink from the dam) which are in direct contrast to public values.…”
Section: The Future Of Surplus Dairy Animalsmentioning
confidence: 99%
“…Surprisingly little research has assessed public values about surplus dairy calves. When asked about food animal agriculture in general, the public strongly values naturalness, such as pasture access as well as indoor environments that allow for the expression of natural behavior, freedom of movement and socializing with companions [reviewed by (117,118)]. The current system for rearing surplus dairy calves is heavily reliant on unnatural housing (e.g., indoor housing with mechanical ventilation or outdoor housing with low space allowance), isolated social environments (e.g., individual pens), and inadequate feeding programs (low milk allowances compared to what they would drink from the dam) which are in direct contrast to public values.…”
Section: The Future Of Surplus Dairy Animalsmentioning
confidence: 99%
“…The status quo of how surplus calves are cared for has, as argued above, primarily been brought about in part because these animals have an inherent low economic value and in part because the dairy industry is focused on the milk production aspects of their industry. However, the rising value attributed to the maintenance of public trust in the dairy industry has initiated discussions about the need to improve the way surplus calves are managed (45,47). Commonly recognized challenges facing agriculture more broadly include a general public that is becoming increasingly disconnected from food production (48), combined with an increase in concern about how food is produced (49,50).…”
Section: The Case For Changementioning
confidence: 99%
“…Since its beginnings, the definition of agroecology has broadened and now addresses the entire food system, understood in its multiple dimensions (Francis et al, 2003) and the multiplicity of social, political and economic issues and actors involved in agricultural transformation (Stassart andJamar, 2008, Doré andBellon, 2019). Agroecological systems need to be productive, input-efficient, socially equitable and economically viable, all at the same time (Altieri, 1995). With a view to reducing environmental impacts and responding to societal expectations and current concerns, the aim of agroecology is therefore to better integrate ecological processes into agricultural systems by replacing chemical and energy inputs by natural processes and by improving biogeochemical cycling (minerals, energy, water).…”
Section: Theoretical Definition Of An Agroecological Systemmentioning
confidence: 99%
“…The global livestock sector currently uses 30% of the planet's land and 32% of its water and generates 18% of greenhouse gas emissions (Steinfeld et al, 2006, Herrero et al, 2015. These production models also draw criticisms from society concerning animal welfare (Webster et al, 2015, Beaver et al, 2020 and the origin and quality of animal feed (Jacquot et al, 2019). Numerous research studies have shown that animals are sensitive beings endowed with cognitive abilities (De Fontenay, 1998).…”
Section: Introductionmentioning
confidence: 99%